CYTOTOXICITY OF SELECTED MEDICINAL PLANTS USED IN MT. FRERE DISTRICT, SOUTH AFRICA - Mnengi, Doris; Kappo, Abidemi; Kambizi, Learnmore; Nakin, Motebang (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: In South African traditional medicine, there are some plants known to combat pediatric diseases and are commonly used by traditional healers. The aim was to evaluate the cytotoxicity effects of the plants.Materials and methods: The ground plant material was exhaustively extracted using methanol, acetone and water separately for 72 hrs. These organic solvents were removed from filtrates using a rotavapour. Stock solutions were prepared at 40 mg/ml Dimethyl sulfoxide (DMSO), and test solutions were transferred into vials and 10 brine shrimps introduced in each. The number of dead shrimps was counted to ascertain toxicity. Ten A. salina nauplii (larva), were transferred into each sample vial and filtered brine solution was added to make 5 ml. The nauplii were counted macroscopically in the stem of the pipette against a lighted background. A drop of dry yeast suspension was added as food to each vial. Probit analysis was used to determine the concentration at which lethality to brine shrimp represents 50 % (LC50).Results: All the tested extracts showed that the concentration was directly proportional to death of brine shrimps. Fifty percent lethality (LC50), of the tested crude extract ranged between 4.1 and 4.6 µg/ml extract with methanol extract of B. abyssinica being the lowest and T. acutiloba the highest. Conclusions: This study revealed that 100% of plant crude extracts screened for activity against Artemisia salina larvae showed strong cytotoxicity below 10 μg/ml and plant species with LC50 values < 1000 μg/ml may not make good paediatric remedies due to their inherent toxicity.